India : Financial Sector Assessment Program-Detailed Assessments Report on IOSCO Objectives and Principles of Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses findings of the assessments on International Organization of Securities Commissions (IOSCO) Objectives and Principles of Securities Regulation for India. India exhibits significant progress in the implementation of the IOSCO Principles vis-a-vis the assessment concluded in 2000. The Securities and Exchange Board of India (SEBI) faces three main challenges that altogether impact the effectiveness of the supervisory programs for issuers and securities intermediaries: strengthening the supervision approach toward securities intermediaries, improving mechanisms to ensure compliance of issuers with reporting requirements, and mechanisms to ensure compliance with accounting and auditing requirements. SEBI is aware of such challenges, and some measures are currently being implemented to address them.